2021
DOI: 10.1007/s12553-021-00595-x
|View full text |Cite
|
Sign up to set email alerts
|

Use and self-perceived effects of social media before and after the COVID-19 outbreak: a cross-national study

Abstract: To (i) examine the use of social media before and after the COVID-19 outbreak; (ii) examine the self-perceived impact of social media before and after the outbreak; and (iii) examine whether the self-perceived impacts of social media after the outbreak varied by levels of mental health. A cross-national online survey was conducted in Norway, UK, USA and Australia. Participants (n = 3810) reported which social media they used, how frequently they used them before and after the COVID-19 outbreak, and the degree … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 38 publications
(44 reference statements)
0
9
0
Order By: Relevance
“…This result corroborates with previous studies elsewhere that have linked the higher levels of exposure to social media with poor mental health outcomes before 27 , 40 , 41 and during the pandemic. 7 , 21 , 23 - 25 , 42 Moreover, we note a higher concentration of respondents reporting the highest level of SMU and worst mental health during the first year of the pandemic versus the second year (2020 > 2021). The decrease of SMU and the improvement of mental status of the respondents may have been influenced by the gradual easing of lockdown measures, similar to what was noted in a previous longitudinal study in Austria.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…This result corroborates with previous studies elsewhere that have linked the higher levels of exposure to social media with poor mental health outcomes before 27 , 40 , 41 and during the pandemic. 7 , 21 , 23 - 25 , 42 Moreover, we note a higher concentration of respondents reporting the highest level of SMU and worst mental health during the first year of the pandemic versus the second year (2020 > 2021). The decrease of SMU and the improvement of mental status of the respondents may have been influenced by the gradual easing of lockdown measures, similar to what was noted in a previous longitudinal study in Austria.…”
Section: Discussionmentioning
confidence: 64%
“…social media) can influence various psychological outcomes. 19 , 20 Based on previous research that indicate parallelisms in the prevalence of SMU and mental health challenges before 21 - 23 and during the pandemic, 24 , 25 we hypothesize that perceived pandemic-related changes in social media use and mental health status before and during the pandemic are significantly associated (H1).…”
Section: Introductionmentioning
confidence: 99%
“…The main finding that stands out here is that the discourse of missing life is tried to be compensated by digitalization. Similar research in the field regarding the impact of Covid-19 pandemic on lifestyles also reveal this social interaction adaptation towards e-socialization especially among young people (Panarese & Azzarita, 2021;Thygesen, et al, 2021;Volkmer, 2021;Bravo-Cucci, et al, 2022). In the transition to the post-pandemic period, it has been found that such an approach has weakened and now tends to elements outside home such as fashion.…”
Section: Resultsmentioning
confidence: 54%
“…Following the lockdown measures of the recent SARS-COV19 pandemic, unhealthy eating patterns and low physical activity have ensued [ 2 ]. Conversely, there has been a boom in social media usage and content, drawing attention to one’s physical appearance and a more acceptable body frame [ 3 ]. The increased internet access during the pandemic has led to a better understanding of the condition due an increase in both pictorial and descriptive information on social media platforms and also greater acceptance of its treatment [ 4 , 5 ].…”
mentioning
confidence: 99%